Graphene and coltan: Development opportunity for the electronics industry in Colombia - Paz Penagos, Hernán
The clean and renewable energy scenario has gone through a transformation process with the discovery of new generation sources and devices for their storage. Sustainable and efficient solutions are sought to satisfy the growing energy demand of today's population. The environmental problems related to fossil fuels are recognized throughout the world, but to abandon them and for renewable energies to cover current demand, they must not only deliver enough energy but must also be accumulated and transported. In this perspective, batteries play an important role in different areas, from energy storage to powering electronic devices, electric vehicles, etc. Electronic devices use relatively little power, so even small improvements in batteries have driven big changes in their performance and daily use. The functionalities of graphene and coltan make them ideal for a variety of applications, which are at the same time development opportunities for Colombia, such as water purification and desalination, catalyzing systems for the production of hydrogen and foams for lighting purposes, and a rapid heating element; graphene used as a photocatalytic coating material in smart buildings can purify the air in cities; It is also a promising material in the fields of printed electronics, sensors, graphene-based field-effect transistor (GFET) biosensors, optical biosensors, and photovoltaic cells. The possibility of incorporating graphene microchips implanted in teeth for bacterial detection and monitoring of oral hygiene is currently being studied, which could facilitate the study and prevention of periodontal diseases in the future; At the University of Manchester, new graphene condoms were obtained thanks to graphene composite polymers, which provide a higher heat transfer rate, improving sensitivity and the ability to disperse active drugs to prevent sexually transmitted diseases uniformly, pregnancy or even increase sexual pleasure. Graphene sheets have also recently been used to measure blood glucose levels through sweat and deliver pharmacological doses through the skin. This research focuses on a case study: the sizing of a Lithium battery with graphite in both electrodes as an alternative solution for greater energy storage. In this process, the participation of graphite in both electrodes is expanded, specifically in the coating of the cathode through layers to reduce losses and thereby improve battery storage. With this proposal, both the anode and the cathode will be made up of intercalator materials (graphite), different from the metallic lithium anode, which is dangerous, and the Li+1 ion can travel reversibly between them. As a result of the work, the structure of the new battery that will be built and tested in the following stages of the research was designed in SolidWorks software.